If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -21 = -6 + 3w Solving -21 = -6 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -21 + -3w = -6 + 3w + -3w Combine like terms: 3w + -3w = 0 -21 + -3w = -6 + 0 -21 + -3w = -6 Add '21' to each side of the equation. -21 + 21 + -3w = -6 + 21 Combine like terms: -21 + 21 = 0 0 + -3w = -6 + 21 -3w = -6 + 21 Combine like terms: -6 + 21 = 15 -3w = 15 Divide each side by '-3'. w = -5 Simplifying w = -5
| 5(y-2)=8 | | 2+4w=26 | | 3x-15=x+15 | | 3y-6=-27 | | 3x-7=(x+4) | | 4x-4=-2 | | 7x-3=-5+6x-(4x+3) | | x^3-2=0 | | 10-8x=27-15x | | -x+11=5x+12-(7x-2) | | S^2-2s-8=0 | | 6x^2+4=10 | | 81-2(x-1)2=51 | | 3x^2-4=4-3x^2 | | -12x-9x=9x+24 | | 2x+5-15+3x=5 | | 6x(5x+3)=18x | | 5k-12=20 | | 2x+4(2x+4)=50 | | 8x-8=3x+4 | | 6x+80=9x-7 | | 12-7x=162-42x | | 129-9x=9x+15 | | 2*x*x+5=10 | | 9+.44444444444=19 | | 6x+83=9x-7 | | 2x^3-x^2-1=0 | | 2+45-3/2=12b | | 8t-5=19 | | 6x-11-7x+12= | | 4x^2-4x+4=0 | | -x^2+x-12=0 |